Projet du parc linéaire de l’humedal Juan Amarillo, 2000-2018, Bogota, Colombie - Eduardo Samper Martinez (Projets de Paysage)
This paper presents an outline of the cultural and eco-systemic context of the wetlands (humedales) of the savannah (sabana) district of the city of Bogota situated at an altitude of 2,600 metres with a surface area of 1,800 square kilometres. Based in one of these wetlands, the Juan Amarillo humedal which is more than 6 km long with a width varying within just a few hundred metres, the aim is to demonstrate the current challenges involved in their development as landscapes and in their proposed uses for a population of close to 2 million inhabitants. These ecological challenges became urban and technical challenges during the 20th century with the channelling and containment of the many rivers (rios) which course through the savannah, causing the loss of the area’s function as a filter and buffer zone for the rainwater and the rios that flow down from the mountains and the paramos. As a result of the intense urban pressure of the last twenty years, these wetlands are in very poor condition and have become even more vulnerable. It is therefore necessary to prevent their degradation and to protect them as areas ensuring an ecological balance (plants, fauna and flora, with the lake waters as a transition area), to make them accessible for leisure activities (walks, games, sports) and to use them for environmental education and for the dissemination of knowledge about local the pre-colonial culture which remains embedded in these areas. The aim is to restore these wetland areas and adapt them to the current urban situation as much as possible, taking into account the knowledge and good use of the natural elements.